Analisis Semiotika Roland Barthes pada Representasi Makna Kehilangan Film “Generasi 90an: Melankolia” - Jakaria, M Ihsan; Mayasari., Mayasari.; Lubis, Flori Mardiani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Film is a mass communication media tool that has a role in this era. Not only for entertainment but can be used as a medium of learning. Regardless of the development of technology and information that continues to develop, it has a similar impact on the development of film in the world. Film becomes a social discourse with unique characteristics that spread to various places, and a film psychoanalyst perspective to influence ways of thinking related to the perception and suitability of values where the information is communicated. Films in general also raise a theme or phenomenon that occurs in the midst of society. One such film is "Generation 90s: Melancholia" produced by Visinema Pictures which was adapted from a book with the same title namely "Generation 90s" written by Marcella FP. Previously, the screening of this film was delayed due to a pandemic, but after a year of delayed screening, finally with the condition of the pandemic having subsided, this film is being shown in several theaters and also Netflix. This film has a deep meaning of loss. Family and friends also feel a deep sense of loss because one of the characters, Indah, who died in a plane crash, was left behind. In this study, researchers used qualitative research methods and descriptive analysis techniques. The theory used is Roland Barthes' Semiotic Theory which consists of denotations, connotations and myths to find the meaning of loss in the film "Generation 90s: Melancholia". Keywords: Semiotic Theory, Roland Barthes, Meaning Loss, Film 90s Generation: Melancholia